Fluorescence Emission Enhancement in Crystalline Photonic Structures - Archana Singh (International Journal of Crystalline Materials, 2024)
One of the two ways that a material that has absorbed light or other electromagnetic radiation can emit light is through fluorescence. Fluorspar is a substance that can be added to welding compounds to facilitate easier flow; the word fluorescent is derived from the Latin fluere, which means "to flow." LED lights, clothing that glows in "black light," or light sources that contain UV or blue light, and butterflies like the swallowtail butterfly are a few examples of fluorescence. The basis of fluorescence lies in certain molecules' ability to absorb photon energy and enter an excited state when struck by one. Fluorescence emission is the photon released by the same molecule when it relaxes from its excited state. Nonetheless, there is a possibility that fluorescence plays crucial roles in coral health, UV protection and antioxidant defense, photo-acclimation, mating, signaling and communication, lures, and camouflage. exhibit the same phenomenon. Bioluminescence is among the best examples of fluorescence found in nature. The tiny bioluminescent phytoplankton in the marine water glows when it is touched.
Keywords: LED lights; bioluminesc phytoplankton; black light; electromagnetic radiation; fluorescent